1989
DOI: 10.1346/ccmn.1989.0370509
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mn2+ and pH on the Formation of Iron Oxides from Ferrous Chloride and Ferrous Sulfate Solutions

Abstract: Abstract--The influence of Mn 2 § on the formation of Fe oxides at pHs of 6.0 and 8.0 and varying Mn/ Fe molar ratios (0, 0.1, 1.0, and 10.0) in the FeC12-NH4OH and FeSO4-NH4OH systems was studied by X-ray powder diffraction (XRD), infrared absorption, transmission electron microscopic, and chemical analyses. In the absence of Mn ~+, lepidocrocite (-t-FeOOH) and maghemite ('y-Fe203) were the crystalline species formed at pHs of 6.0 and 8.0, respectively, in the FeC12 system, whereas lepidocrocite and goethite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…2a). The results are in agreement with Krishnamurti and Huang study [17] who concluded that poorly-crystalline iron oxides are formed when a minor amount of citrate was introduced into solution.…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…2a). The results are in agreement with Krishnamurti and Huang study [17] who concluded that poorly-crystalline iron oxides are formed when a minor amount of citrate was introduced into solution.…”
Section: Methodssupporting
confidence: 91%
“…The introduction of citrate ions into solution create relatively stable Fe(II)-ligand complexes. Such complexes decrease the rate constant of Fe(II) oxidation and thus, influent the form of precipitated iron compounds [17]. In case of NH 4 Cl catalyst, the iron compounds were identified as FeO(OH) and Fe 3 O 4 (Fig.…”
Section: Methodsmentioning
confidence: 98%
“…With time, the green rust was completely oxidized and then rapidly converted into a yellow brown precipitate, which on further oxidation resulted in the formation of goethite nanoparticles. Without HA, the precipitation products after 8 years of aging at pH 5.0 gives rise to an intermediate product of ferrihydrite and goethite (Krishnamurti and Huang, 1989). In the presence of small amounts of HA (R = 0.001), however, coprecipitation probably modified the stacking of the hydroxyl sheets resulting in the formation of lepidocrocite instead of goethite.…”
Section: Influence Of Humic Acid On the Oxidative Products Of Fe 2+mentioning
confidence: 99%
“…In laboratory systems, the oxidation of Fe 2+ solutions in the absence of complexing ligands yields goethite (α-FeOOH) and lepidocrocite (γ-FeOOH) in mildly acidic environments (pHs of 4.0-6.0) and magnetite (Fe 3 O 4 ) in mildly alkaline conditions (pHs of 7.0-8.0) (Schwertmann and Taylor, 1989;Taylor and Schwertmann, 1974). In laboratory hydrothermal synthesis, many complexing ligands are capable of altering the rate of Fe 2+ oxidation, resulting in different Fe precipitation products, namely green rust (Krishnamurti and Huang, 1989, 1991, 1993Schwertmann and Fechter, 1994). Cornell and Schwertmann (1979) showed that citrate inhibited the conversion of ferrihydrite to goethite and promoted the crystal growth of lepidocrocite at the expense of goethite.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the effect of foreign ions may give a better understanding of the mechanisms of formation, the structure, and phase transformations. The chemical similarity between Mn and Fe makes Mn a logical element to investigate. The influence of manganese on the formation of akaganeite was studied in this paper.…”
Section: Introductionmentioning
confidence: 99%